Armageddon time [videorecording (DVD)] - Gray, James, 1969-; Hathaway, Anne, 1982-; Strong, Jeremy, 1978-; Repeta, Banks; Webb, Jaylin; Feldshuh, Tovah; Diehl, John, 1950-; Polk, Andrew; Hopkins, Anthony, 1937-; Khondji, Darius; Morris, Scott; Spelman, Christopher (Universal, 2023)
A deeply personal coming-of-age story about the strength of family and the generational pursuit of the American Dream.